Institutionalized Association of Southeast Asian Nations-Our Eyes Cooperation at the Ministry of Defense of the Republic of Indonesia Within the Framework of Defense Diplomacy - Pakpahan, Merjames; Yusgiantoro, Purnomo; Mahroza, Jonni; Saragih, Herlina JR (Graduate Program Magister Manajemen Pendidikan, 2023)
Institutional which is made into the rule of game and organization, has a very important and decisive role in making arrangements in allocating resources efficiently, equitably and sustainably. The dimension aspect of organizational structure has three sub-dimensions namely complexity, formalization, and centralization. This research uses explanative qualitative methods. Data collection was obtained through secondary sources and analyzed by means of data comparison, verification, and drawing conclusions. The ASEAN Our Eyes organization as an institution in the Ministry of Defense of the Republic of Indonesia which has begun its formation but is still looking for a format that can run effectively and efficiently carry out its mission in order to safeguard Indonesia's national interests in the operationalization of bilateral and multilateral cooperation within the framework of defense diplomacy. Efforts to institutionalize ASEAN Our Eyes in the dimensions of a modern organizational structure, through a review of several sub-dimensions, are based on short-term needs. The discussion in this study will provide an overview of the design of the Indonesian Ministry of Defense's ASEAN Our Eyes institutional model, which is effective in achieving national interests in all future forms of defense cooperation.